First International Seminar on Physical Infrastructure (1st ISPI) (2022)
The First International Seminar on Physical Infrastructure (1st ISPI) was an academic and scientific event organized by the Road Infrastructure Research Group and the Road Infrastructure Research Seedbed of the Universidad Francisco de Paula Santander, San José de Cúcuta, Colombia; the 1st ISPI was held from October 13 to 15, 2021. The purpose of the 1st ISPI was to allow the academic and scientific community, researchers, professors, professionals, and students, to share results and research proposals in the areas of Engineering, Mathematics, and Physics; during the 1st ISPI is presented 29 research work, of which 6 were plenary lectures from Spain, Brazil, Venezuela, and Colombia, and 23 talks, on different topics that allowed to the participants the to learn about the current state of the Physical Infrastructure, the Mathematical Modeling, the Physical and Numerical Modeling, the Physicochemical Phenomena in Engineering, the Advances in Materials Science and Engineering, the Simulation of PhysicalMathematical Problems in Engineering, and the Teaching and Research Techniques in Science and Engineering. The website of the conference is available at https://foristom.org/1ispi. On behalf of the organizing committee of the 1st ISPI, we are extremely thankful to all authors and participants for providing their valuable contributions to this Proceedings volume as well as the reviewers for their constructive recommendations and criticism aiding to improve the presented articles. Likewise, we like to thank the Universidad Francisco de Paula Santander, and the Foundation of Researchers in Materials Science and Technology, for all the support technical and logistical received. Likewise, the organizing committee 1st ISPI thanks all who attended this edition of the event, and we are very proud to have carried out this event successfully that allowing the generation and effective transfer of new knowledge regarding the topics addressed during the event; we will be waiting for you at the 2nd ISPI in 2022. Finally, the editor hopes that those interested in the area of physical infrastructure can enjoy this reading, of the volume of the Journal of Physics: Conference Series (JPCS), which reflects a wide variety of current issues.